VARIATION IN GASTROCNEMIUS AND HAMSTRINGS MUSCLE ACTIVITY DURING PEAK KNEE FLEXOR FORCE AFTER ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION WITH HAMSTRING GRAFT: A PRELIMINARY CONTROLLED STUDY (International Journal of Physiotherapy, 2020)
Background: The optimization of this return to athletic activity passes by a better understanding of the muscle's behavior involved in knee function. In this study, we focused on the muscle's muscular activity involved in the flexion of the knee. Precisely on the relation between the gastrocnemius's muscular activity and the hamstring among the patient that underwent an anterior cruciate ligament reconstruction with a hamstring graft.The study's objective is to compare the muscular activity of the flexor knee muscle in patients who underwent an anterior cruciate ligament reconstruction with hamstring autograft and the individuals who have not undergone surgery.Methods: The participants have been divided into two groups: a healthy group and an experimental group that underwent an anterior cruciate ligament reconstruction with a hamstring graft. The participants had to perform a strength test on an isokinetic dynamometer. The medial gastrocnemius activity, lateral gastrocnemius, femoral biceps, and the semitendinosus were measured during this test.The first group individuals mentioned the muscle's muscular activity compared to those in the second group via statistical analysis. Then, a ratio of the gastrocnemius muscle activity on the activity of the hamstring has calculated. The results of the experimental group were then compared to the results of the control group.Results: The results showed a significant difference in activity of the medial gastrocnemius (p = 0,004901), the biceps femoris (p = 5,394.10-6), and the semitendinosus muscles (p = 1,822.10-6 ): the experimental group results were superior to the control group results. However, the evaluation of the activity reporting has shown significant differences in the two groups.Conclusion: This study has shown a difference in the gastrocnemius and hamstring muscle activity between patients who underwent an anterior cruciate ligament reconstruction surgery and healthy participants. However, our approach has not allowed us to identify the relationship between a heightened gastrocnemius activity and a diminished hamstring activity following an anterior cruciate ligament reconstruction with a hamstring graft. Quite on the contrary, we observed higher activity of the two muscle groups.Nevertheless, it seems necessary to have a variation in situations during the gastrocnemius muscle analysis to fully understand its purpose in the functional activity of the knee of patients who have undergone an anterior cruciate ligament reconstruction.